Epigenetic Regulation of a Disintegrin and Metalloproteinase (ADAM) Transcription in Colorectal Cancer Cells: Involvement of β-Catenin, BRG1, and KDM4 - Sun, Lina; Chen, Baoyu; Wu, Jiahao; Jiang, Chao; Fan, Zhiwen; Feng, Yifei; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
A disintegrin and metalloproteinase (ADAM) family of proteins play versatile roles in cancer development and progression. In the present study we investigated the role of ADAM proteins in colorectal cancer (CRC) cell migration and invasion focusing on the epigenetic mechanism whereby ADAM transcription is regulated. We report that ADAM10, ADAM17, and ADAM19 were higher in SW480 cells than in HCT116 cells. Expression levels of the same set of ADAMs were higher in human CRC biopsy specimens of advanced stages than in those of a less aggressive phenotype. Over-expression of ADAM10/17/19 in HCT116 cells enhanced whereas depletion of ADAM10/17/19 in SW480 cells weakened migration and invasion. ADAM expression was activated by the Wnt signaling pathway, which could be attributed to direct binding of -catenin on the ADAM promoters. Mechanistically, -catenin recruited the chromatin remodeling protein BRG1, which in turn enlisted histonedemethylase KDM4 to alter the chromatin structure thereby leading to ADAM trans-activation. In conclusion, our data suggest that the Wnt signaling may promote CRC metastasis, at least in part, by recruiting an epigenetic complex to activate ADAM transcription.